2017
DOI: 10.1073/pnas.1704856114
|View full text |Cite
|
Sign up to set email alerts
|

Simulating tactile signals from the whole hand with millisecond precision

Abstract: When we grasp and manipulate an object, populations of tactile nerve fibers become activated and convey information about the shape, size, and texture of the object and its motion across the skin. The response properties of tactile fibers have been extensively characterized in single-unit recordings, yielding important insights into how individual fibers encode tactile information. A recurring finding in this extensive body of work is that stimulus information is distributed over many fibers. However, our unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
251
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(273 citation statements)
references
References 76 publications
(112 reference statements)
8
251
1
3
Order By: Relevance
“…As a further rationale that passive tactile stimulation may provide a restricted view of somatosensory activity, the somatosensory cortex receives inputs from a host of sources beyond the simple cutaneous touch activated by passive tasks. This includes activation of deep mechanoreceptors, muscle proprioceptors, and skin stretch receptors (Bensmaia & Tillery, 2014;Chouvardas, Miliou, & Hatalis, 2008;Saal, Delhaye, Rayhaun, & Bensmaia, 2017). Active movement also causes efferent signals into SI from the motor system (Wolpert & Flanagan, 2001;Wolpert, Ghahramani, & Jordan, 1995), as well as top down inputs from high-order cognitive processing, e.g., attention, visual input (Kuehn, Mueller, Turner, & Schütz-Bosbach, 2014;Puckett, Bollmann, Barth, & Cunnington, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a further rationale that passive tactile stimulation may provide a restricted view of somatosensory activity, the somatosensory cortex receives inputs from a host of sources beyond the simple cutaneous touch activated by passive tasks. This includes activation of deep mechanoreceptors, muscle proprioceptors, and skin stretch receptors (Bensmaia & Tillery, 2014;Chouvardas, Miliou, & Hatalis, 2008;Saal, Delhaye, Rayhaun, & Bensmaia, 2017). Active movement also causes efferent signals into SI from the motor system (Wolpert & Flanagan, 2001;Wolpert, Ghahramani, & Jordan, 1995), as well as top down inputs from high-order cognitive processing, e.g., attention, visual input (Kuehn, Mueller, Turner, & Schütz-Bosbach, 2014;Puckett, Bollmann, Barth, & Cunnington, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We wonder whether the observed insensitivity to the higher-order statistics reflects processing characteristics of the central nervous system or simple information loss in the periphery, i.e., the elasticity of the skin and noisy sparse sampling by mechanoreceptors. To make our best guess of how the difference in spatial texture information is represented in peripheral neural activation, we simulated responses of tactile afferents using the computational model 'TouchSim' (Saal et al, 2017). The beauty of this model is that it can provide the responses of hundreds of distributed afferents on a millisecond scale, though it works under some simplified assumptions (e.g., it does not incorporate lateral sliding/forces).…”
Section: Simulation Of Skin Deformation and Neural Activity In Peripherymentioning
confidence: 99%
“…We simulated the spike timings and spatial distributions of the afferents while the index finger pad scanned our subband-matched NS stimuli. We calculated the firing similarity across stimuli in terms of a spike distance metric (Victor and Purpura, 1997), following the original 'TouchSim' study (Saal et al, 2017). We found that the firing similarities between pairs of identical texture stimuli with independent neural noise were always higher than those between pairs comprising two different stimuli, regardless of the type of afferent (Fig.…”
Section: Simulation Of Skin Deformation and Neural Activity In Peripherymentioning
confidence: 99%
See 2 more Smart Citations